Digitization of weekly Murrumbidgee River heights at Hay South Eastern Australia 1873–2017. (29th October 2018) - Speer, M. S.
Abstract : Long‐term, high‐frequency river height measurements provide a direct method of relating changes in local water availability in a catchment to such phenomena as climate and changes in land use. Here, digitized weekly river height data from the Murrumbidgee River at Hay in south eastern Australia are presented for the first time covering the start of record from November 1873 to June 2017. There are two gauge board locations: (a) The town gauge at the southern edge of the township with data until March 1983, and (b) the Hay Private Irrigation District (PID) gauge on the north eastern outskirts of Hay about 2 km upstream from the Hay town gauge. There is a data overlap of about 13 years for the two locations. The underlying data quality is good taking into account missing values, outliers, continuity between the two gauge locations and measurement practice. The weekly data are available in both annual and seasonal files. Open Practices: This article has earned an Open Data badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available athttp://doi.org/10.5281/zenodo.1184869 . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .